Correlation between MDA Level and Chitotriosidase-1 Activity in Seminal Fluid of Iraqi Infertile Males - Abdul Aziz, Ali S.; Elyaseen, Hedef D.; Kadhem, Hussain K. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Male infertility is a multifactorial condition influenced by various physiological and biochemical factors. Seminal fluid composition plays a crucial role in sperm function and fertilization potential. Chitotriosidase is a chitinase enzyme released by activated macrophages and is highly conserved and controlled. The notable chitinase in humans plays a significant role in the body’s immunological response and is linked to inflammation, infection, tissue damage, and remodeling processes. On the other hand, malondialdehyde is a marker of lipid peroxidation, reflecting oxidative stress levels. Objective: This study aimed to explore the correlation between malondialdehyde levels and Chitotriosidase-1in seminal fluid in Iraqi infertile males. Methods: Ninety males aged between twenty and forty-five were included in this cross-sectional study, all diagnosed with infertility by specialists at the infertility unit of Al-Batool Teaching Hospital between February 2022 and February 2023. The participants were categorized into three groups: the Normozoospermic Group (G1), the Asthenospermia Group (G2), and the Oligozoospermic Group (G3). Seminal malondialdehyde and Chitotriosidase-1 levels were measured by competitive Enzyme-linked immunosorbent assay. Results: The study findings showed significantly higher levels of seminal fluid Chitotriosidase-1 found in the G2 group compared to the G3 and G1 groups. The seminal fluid malondialdehyde level for G1 was significantly lower than those for G2 and G3, which revealed a significant positive correlation between seminal fluid Chitotriosidase-1 activity and malondialdehyde levels (r = 0.37, P < 0.05) in the Asthenospermia Group. Conclusion: There is a correlation between seminal fluid Chitotriosidase-1 activity and malondialdehyde level in the Asthenospermia Group. Novel diagnostic and therapeutic approaches for the treatment of male infertility may result from our growing understanding of the roles played by Chitotriosidase-1 and malondialdehyde in male reproductive health.